Formulation And Physical Properties Testing Of Lip Tint Preparations Of Akalifa Leaf Extract (Acalypha Wilkeisiana Mueill. Arg) - Mayasari, Shinta; Siti Nur Maulita; Ayu Angger Putri M. Soleh; Fendy Prasetyawan; Arista Wahyu Ningsih (Jurnal EduHealth, 2025)
Cosmetics are preparations of several ingredients for external use such as skin epidermis, hair, nails, lips, teeth and oral cavity. Lip tint is a lip coloring product that helps lips become more colorful and fresher. One of the plants that can be used as a natural dye is akalifa leaves (Acalypha wilkeisiana Müeill. Arg.). Based on research, akalifa leaves contain chemicals, namely, saponins, flavonoids, tannins, polyphenols, alkaloids. To make formulations and test the physical properties of lip tint preparations with concentrations of 10%, 13%, 16%.This research method uses a laboratory experimental design. The sample used in this research was akalifa leaf extract which was obtained by the maceration extraction method using 96% ethanol solvent. Physical property tests carried out include organoleptic tests, homogeneity tests, pH tests, irritation tests, spreadability tests, hedonic tests. The data will then be analyzed with one way ANOVA tests and LSD tests. The formulation results from concentrations of 10%, 13%, 16% which were liked by many panelists were F3. Evaluation of the physical properties of organoleptic tests on 4 lip tint preparations of akalifa leaf extract and one of them without extract (blank) has a clear color (F0), pink color (F1), red color (F2), deep dark red color (F3). The results of the irritation test at F0 – F3 showed that there was no irritation among the panelists. The parameters for protecting against irritation reactions were reviewed based on the presence of mild erythema, clear erythema, and strong erythema. The lip tint formulation with a concentration of akalifa leaf extract  16% (F3) was most preferred by the panelists. The physical properties observed include organoleptic tests, homogeneity tests, pH tests, irritation tests, spreadability tests, and liking tests, all of which show good results and are safe to use.